2014
DOI: 10.1530/eje-13-1006
|View full text |Cite
|
Sign up to set email alerts
|

Extreme phenotypic variability of thyroid dysgenesis in six new cases of congenital hypothyroidism due to PAX8 gene loss-of-function mutations

Abstract: Context: Within the last two decades, heterozygous loss-of-function PAX8 mutations have been reported in patients with a wide degree of thyroid gland dysfunction and growth despite the presence of identical mutations. Objectives: To search for PAX8 mutations in a cohort of patients with congenital hypothyroidism (CH) and various types of thyroid gland defects. Design: A cross-sectional study was conducted in a cohort of patients. Setting: The French neonatal screening program was used for recruiting patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…TUBB1 mutations constitute a model of dominant inheritance of CH with TD. Most known mutations responsible for TD and previously described TUBB1 mutations causing macrothrombocytopaenia are also dominant (Kunishima et al , , ; Guillot et al , ; Ramos et al , ; Carré et al , ; Fiore et al , ). Our data indicate high penetrance for platelet alterations and incomplete penetrance with variable expressivity for TD, ranging from TD without CH to TD with CH and leading to variable types of TD (ectopia, hypoplasia, hemithyroid or asymmetric thyroid gland).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…TUBB1 mutations constitute a model of dominant inheritance of CH with TD. Most known mutations responsible for TD and previously described TUBB1 mutations causing macrothrombocytopaenia are also dominant (Kunishima et al , , ; Guillot et al , ; Ramos et al , ; Carré et al , ; Fiore et al , ). Our data indicate high penetrance for platelet alterations and incomplete penetrance with variable expressivity for TD, ranging from TD without CH to TD with CH and leading to variable types of TD (ectopia, hypoplasia, hemithyroid or asymmetric thyroid gland).…”
Section: Discussionmentioning
confidence: 98%
“…Abnormalities at any step of thyroid development may result in TD associated with hypothyroidism or not (Maiorana et al , ). Previous studies of sporadic and familial TD covering a wide clinical spectrum identified mutations in nine genes: PAX8 , NKX2‐1 , FOXE1 , NKX2‐5 , TSHR, GLIS3, NTN1 , JAG1 and BOREALIN (Dentice et al , ; Senée et al , ; Carré et al , , , ; Sura‐Trueba et al , ; Ramos et al , ; Opitz et al , ; de Filippis et al , ). However, mutations in these genes are found in only 5% of all patients with TD and identification of causative mutations remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…The first is due to the phenotypic heterogeneity (either inter or intra‐familial) of subjects harboring mutation of the same gene. It has been widely shown, for example, that TD due to mutations in PAX8 NKX2‐1 displayed a variable thyroid phenotype. Furthermore, a second cause could be found in the genetic heterogeneity of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of RTSH-associated PAX8 promoter variants [6971], the observation of a frameshift mutation with demonstrated protein instability [72], and the autoregulation of PAX8 by binding to its own promoter [73] are also consistent with a haploinsufficiency mechanism. A noteworthy mutational hotspot is the CpG dinucleotide at codon 31, for which frequent mutational events (R31H and R31C) have been reported [61, 65, 67, 7477]. For some of the reported mutations, the primary defect is the impaired synergism with other thyroid transcription factors (NKX2-1) or insufficient recruitment of coactivators (p300) without altering DNA binding [7880].…”
Section: Rtsh Due To Loss-of-function Mutations In Pax8mentioning
confidence: 99%